2022
DOI: 10.3390/molecules27175598
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Versus Preventative Use of Ginkgo biloba Extract (EGb 761) against Indomethacin-Induced Gastric Ulcer in Mice

Abstract: The main bioactive constituents in the standardized Ginkgo biloba leaf extract (EGb 761) are the terpene lactones and flavonoid glycosides. EGb 761’s antioxidant and anti-inflammatory properties have previously been demonstrated. Indomethacin-induced gastric ulcers have a multifactorial etiology and represent a major restriction to its therapeutic utility. The underlying ulcerogenic process involves oxidative and inflammatory biomolecular insults. This study was performed to explore the curative and preventati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…The staining procedure (Abd‐Eldayem et al, 2022) was as follows: Blocking serum (Dako) was applied for 5 min at room temperature to block non‐specific background staining, followed by incubation in a primary antibody (Table 2). After incubation, the slides were washed with PBS (pH 7.4, three times × 5 min), followed by incubation with secondary antibody (Table 2) for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The staining procedure (Abd‐Eldayem et al, 2022) was as follows: Blocking serum (Dako) was applied for 5 min at room temperature to block non‐specific background staining, followed by incubation in a primary antibody (Table 2). After incubation, the slides were washed with PBS (pH 7.4, three times × 5 min), followed by incubation with secondary antibody (Table 2) for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Negative imaging (as shown in the Supplementary Figures) was undertaken using CMEIAS Color Segmentation, an improved computing technology used to process color images by segmenting the foreground object of interest from the background (Gross et al, 2010). This was achieved following the manufacturer's instructions and as previously published (Abd‐Eldayem et al, 2022; Grover et al, 2002; Mustafa et al, 2022; Mustafa & El‐Zahraa, 2019; Soliman, Abd‐Elhafeez, et al, 2022; Soliman, Emeish, & Abdel‐Hafeez, 2022; Yousef et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…antioxidant properties, making them valuable in the management of various disorders [85]. Additionally, T. aphylla has been found to have diverse biological importance, including antiinflammatory, antibacterial, antifungal, treatment of periodontal diseases, anticholinesterase, analgesic, anti-diabetic, and cytotoxic activities [35].…”
Section: Plos Onementioning
confidence: 99%
“…In contrast to the control group, the rats that were subjected to indomethacin displayed heightened levels of IL-1β, IL-6, and TNF-α [96]. Prior research has found compelling evidence of a significant rise in proinflammatory cytokines in indomethacin induced gastric ulcer emphasizing the crucial role of pro inflammatory cytokines in the development of gastric ulcer [85,97,98]. Pre-treatment with a crude leaf extract of T. aphylla, in contrast, exhibited inhibitory effects on the upregulation of TNF-α, IL-1 β, and IL-6 levels, and even restored these cytokines to their baseline levels.…”
Section: Plos Onementioning
confidence: 99%